Living Environs and Nutritional Status of Children from an Urban Indian Slum: An Analysis of Associative Factors - Kulsum, Asma; Lakshmi, A. Jyothi; Prakash, Jamuna (International Journal of Child Health and Nutrition, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Growing urbanization gives rise to slums, which are densely populated peri-urban areas housing underprivileged populations. The nutritional status of children in slum areas can be compromised due to poor living environs despite availability of many urban health care facilities. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The present cross- sectional study was undertaken to determine the nutritional status of children residing in slum and analyze the various associative factors. The study area was Ghousianagar, a slum in city of Mysore from South India. A sample of 676 children (2-11 years of age, males, 310 and females, 366) from two schools was chosen for detailed anthropometry. Data were also collected on living conditions, economic and literacy levels of parents and nutritional status of mothers (n=200) through standard techniques. The results revealed that the living conditions of children were highly unhygienic. Only in 36% of families both parents were literate. Children from all age groups exhibited different degrees of malnutrition which worsened with increasing age. Only 8% of children were normal and the rest suffered with different degrees of undernutrition. Stunting and wasting were significantly influenced by age and gender of children. Under associative factors studied, weight for age of children was significantly associated with economic status of family and maternal BMI. Weight for height was associated with economic status, family size and maternal BMI. Height for age exhibited marginal association with family size. It can be said that adverse living environment and limited resources influenced the nutritional status of children adversely.